Gestión de inventarios y rentabilidad en empresas comerciales rubro cuidado personal, Iquitos, año 2021 - Apagüeño Campos, Stephany Cristina (2022)
Inventory management and profitability are aspects that always require attention in companies, the first because it is the basis of the marketing of products with the purpose of obtaining benefits and the second as an indicator that influences and concerns the partners or actions in In all organizations, the present study considers as a general objective to analyze how inventory management is related to profitability in commercial companies in the personal care sector, Iquitos, year 2021, with a quantitative, descriptive and non-experimental design approach. correlational type, there was the participation of 2 companies in the commercial sector with 60 collaborators, for the collection of data a Likert-type questionnaire was used for the variable inventory management with a reliability of Cronbach's Alpha of 0.873 and a form of data collection for the profitability variable the study identified that good inventory management is perceived in 89% of participants, taking into account their organization, the management of orders, costs, storage and inventory control, however there is still a significant percentage of collaborators who consider that inventory management has shortcomings, in relation to the profitability indicators, results considered low are obtained in relation to assets, equity, income and cost of sale, when performing the statistical analysis it is obtained that the correlation coefficient "r" of Pearson is -0.030, with a significance of 0.820 per which concludes that there is no relationship between inventory management and profitability in commercial companies in the personal care category.